Metabolic Control of Astrocyte Pathogenic Activity via cPLA2-MAVS - Chao, Chun-Cheih; Gutierrez-Vazquez, Cristina; Rothhammer, Veit; Mayo, Lior; Wheeler, Michael A.; Tjon, Emily C.; Zandee, Stephanie E. J.; Blain, Manon; De Lima, Kalil Alves; Takenaka, Maisa C.; Avila-Pacheco, Julian; Hewson, Patrick; et al. (Cell, 2019)
By exploring the immunometabolic pathways that drive pro-inflammatory astrocyte activities, sphingolipid metabolism is identified as a promising therapeutic target in CNS inflammation.
CRIS-Team Scopus Importer:2020-09-22
Keywords: astrocytes; cPLA2; lactate; lactosylceramide; MAVS; metabolism; Miglustat; multiple sclerosis; neuroinflammation; NF-κB